Growth, sustainability, and India's economic reforms - Srinivasan, T. N., 1933- (New Delhi : Oxford University Press, 2011)
This text provides a comprehensive review of the policies and performance of the Indian economy from a historical and comparative perspective. It analyses the origin, rationale, and outcomes of India's economic reforms of 1991 in the context of changes in economy, polity, and society.
Includes bibliographical references.
Description based on print version record.
Keywords: Economic development -- India; Sustainable development -- India; India -- Economic conditions -- 1947-; India -- Economic policy -- 1947-